2017
DOI: 10.1111/ina.12397
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and human exposure assessment of organophosphate flame retardants in indoor dust from various microenvironments of the Rhine/Main region, Germany

Abstract: We analyzed organophosphate flame retardants (OPFRs) in 74 indoor dust samples collected from seven microenvironments (building material markets, private cars, daycare centers, private homes, floor/carpet stores, offices, and schools) in the Rhine/Main region of Germany. Ten of 11 target OPFRs were ubiquitously detected, some with more than 97% detection frequency, including tris(1,3-dichloroisopropyl)phosphate (TCIPP), tris(2-butoxyethyl)phosphate (TBOEP), triphenyl phosphate (TPHP), and tris(isobutyl) phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 70 publications
6
31
1
Order By: Relevance
“…In our study, concentrations of the phthalates and BFRs that are being phased out were generally lower in comparison with previous studies of European preschools [124,126,129,130,131,132]. Furthermore, the levels of TDCIPP and TPHP were similar to previously reported levels in preschool, whereas the levels of TBOEP were somewhat lower [122,123,124,125,128,129].…”
Section: Concentrations In Dustsupporting
confidence: 75%
See 2 more Smart Citations
“…In our study, concentrations of the phthalates and BFRs that are being phased out were generally lower in comparison with previous studies of European preschools [124,126,129,130,131,132]. Furthermore, the levels of TDCIPP and TPHP were similar to previously reported levels in preschool, whereas the levels of TBOEP were somewhat lower [122,123,124,125,128,129].…”
Section: Concentrations In Dustsupporting
confidence: 75%
“…Higher levels of TBOEP in preschools and schools compared to home environments have been reported in several studies [122,125,129,239]. It has been suggested that this is due to the use of floor polish in these public environments.…”
Section: Cleaningmentioning
confidence: 85%
See 1 more Smart Citation
“…The concentrations of PEFRs measured in indoor air were generally around tens to hundreds of ng/m 3 . Higher PEFR levels in indoor air or dust have occasionally been reported in occupational settings (e.g., recycling of electronics) or microenvironments (e.g., cars) (Wu et al, 2016;Ali et al, 2017;Zhou et al, 2017;Bello et al, 2018;Björnsdotter et al, 2018). Concentrations in outdoor air are approximately 1 to 4 orders of magnitude less than in indoor air (Wei et al, 2015).…”
Section: Environmental Occurrence and Routes Of Exposurementioning
confidence: 97%
“…Numerous other worker groups are expected to be more heavily exposed than the general population, especially when workers are in direct contact with large volumes of PEFRs as pure chemicals or at high concentrations in technical formulations at industrial sites and in manufacturing (e.g., at electronics dismantling facilities or electronic goods recycling areas). Measurements of PEFRs in air and dust in various occupational settings have also shown that the work environment may noticeably contribute to external exposure to PEFRs (Makinen et al, 2009;Ali et al, 2014;Wei et al, 2015;Zheng et al, 2017;Zhou et al, 2017;Muenhor et al, 2017;Bello et al, 2018;Ceballos et al, 2018;. Nevertheless, information on the nature and extent of occupational exposures to PEFRs, especially in terms of measurements of an individual's internal exposure, is still limited and warrants further investigations (characterization, quantification, and contribution to total PEFR burden).…”
Section: Workersmentioning
confidence: 99%